Efektivitas Penerapan Electronic Traffic Law Enforcement (E-TLE) dalam Penegakan Aturan Lalu Lintas di Kota Denpasar - Antari, Putu Eva Ditayani; Valensia Angel Yoshe Situmorang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The application of E-ticket technology has become an innovative effort in enforcing traffic laws in various cities in Indonesia, including Denpasar. This research aims to examine the effectiveness of implementing E-tickets in law enforcement in the city of Denpasar, with a focus on its effect on reducing traffic violations, increasing public compliance with traffic rules, and its impact on the effectiveness of law enforcement. The problem raised by the author is regarding obstacles or obstacles in the implementation and effectiveness of E-TLE in law enforcement in the city of Denpasar. Apart from that, this research also aims to answer the question about how effective the implementation of E-TLE is in law enforcement in the city of Denpasar. The research method used by the author is a historical approach and a comparative approach. Data was collected through surveys of the public, analysis of electronic ticket data, and interviews with related parties, such as law enforcement officers and road users. This method was chosen to obtain a comprehensive understanding of the implementation of E-TLE and its impact on traffic law enforcement in Denpasar. The results of this research include an evaluation of the effectiveness or not of the implementation of E-TLE in Denpasar City. From analysis of electronic ticket data and surveys of the public, researchers can evaluate the level of road user compliance with traffic rules after the E-TLE system is introduced, as well as identify obstacles or obstacles that may hinder the effectiveness of implementing this technology.